Virulence factors released by extracellular vesicles from Cryptococcus neoformans - Wenhao Xiao; Huiqiang Lu; Bowei Jiang; Yaqi Zheng; Puwen Chen; Xiaotong Liu; Junyun Huang (Frontiers in Cellular and Infection Microbiology)
Cryptococcus neoformans, a prominent opportunistic pathogen, is equipped with unique mechanisms to evade host immune defenses, notably through its capsule and the secretion of extracellular vesicles (EVs). Despite significant understanding of its pathogenesis, the precise role of EVs in virulence and their molecular components remain underexplored. This review synthesizes current research on the virulence factors encapsulated within EVs of Cryptococcus, highlighting their contribution to fungal survival and pathogenicity. By analyzing the biochemical composition of these vesicles, we found the presence of enzymes (e.g., Urease, laccase), toxins (e.g. Melanin), and genes (e.g. Ssa1) associated with pathogenicity factors. Furthermore, we discuss the implications of these findings for developing therapeutic interventions. This work advances the field by providing a comprehensive overview of EV-mediated mechanisms in Cryptococcus, offering new insights into potential targets for antifungal strategies.